Empowering young minds: enhancing self-confidence in 5th-grade elementary students through positive self-talk - Wisda Via Nurfallah; Indri Gemi Nastiti Hadi; Nabila Setio Lestari; Izza Fadhlinah Dirham; Yulia Ayriza (Insight: Jurnal Ilmiah Psikologi, 2024)
Self-confidence is crucial for students to unlock their potential and enhance personal growth. However, some students struggle with low self-confidence, shyness, and anxiety when expressing their opinions in the classroom. Individuals with low self-confidence may experience negative emotions and self-perceptions. This research investigates the impact of self-talk techniques on boosting students' self-confidence. This study falls into the category of quasi-experimental with a one-group pretest-post-test design. The participants in this research were seven 5th-grade elementary school students who exhibited low self-confidence. Self-confidence assessment was conducted using a ten-item scale based on Lauster’s Theory. Subsequently, the data were subjected to descriptive analysis and the Sign Test. This study's findings reveal positive self-talk techniques can enhance students' self-confidence. These results offer valuable insights to educators, teachers, and other stakeholders, shedding light on effective strategies to assist students in overcoming their fears and anxieties while helping them realize their full potential through straightforward psychological methods like positive self-talk techniques. Keyword: Self-confidence; positive self-talk; elementary students.